Deforestation in Central Chile Causes a Rapid Decline in Landscape Connectivity for a Forest Specialist Bird Species - Vergara-Egert, P; Perez-Hernandez, C; Soto-Gonzalez, G (2013)
The abundance of woodland birds in fragmented forest landscapes may depend on the properties of patch networks. Understanding the consequences of deforestation on woodland birds, therefore, necessarily requires determining which changes in landscape structure make a major contribution to the degradation and subdivision of patch networks. In this study, we addressed how accelerated deforestation in central Chile has modified the landscape structure and function for thorn-tailed rayaditos-a woodland specialist bird. Using a graphical approach based on the habitat use and movement patterns of rayaditos, we quantified the reduction of the internal connectivity of components (i. e., connected patch networks) in the last two decades and determined the main mechanisms responsible for this connectivity loss. Forest cover decreased 61. 7 % between 1989 and 2009. The component size, the fraction of components with ?1 occupied patches and the number of patches per component experienced a large decline during the study period. Over time, most forest cover (ca. 80 %) was contained in only two components. The connectivity of components decreased steeply by 90 %. Only the loss of large patches made a highly significant contribution to explaining changes in connectivity, while the removal of stepping stones was marginally significant. The conversion of forest both to shrubland and to peri-urban areas were the only land-use variables explaining connectivity change with effects that changed over time. Conservation measures to ensure persistence of rayaditos populations in central Chile should be focused on the retention of key elements for connectivity. © 2013 The Ecological Society of Japan.